The Hsf1-sHsp cascade has pan-antiviral activity in mosquito cells - Jieqiong Qu; Michelle Schinkel; Lisa Chiggiato; Samara Rosendo Machado; Gijs J. Overheul; Pascal Miesen; Ronald P. van Rij (Communications Biology)
Abstract Aedes mosquitoes transmit pathogenic arthropod-borne (arbo) viruses, putting nearly half the world’s population at risk. Blocking virus replication in mosquitoes is a promising approach to prevent arbovirus transmission, the development of which requires in-depth knowledge of virus-host interactions and mosquito immunity. By integrating multi-omics data, we find that heat shock factor 1 (Hsf1) regulates eight small heat shock protein (sHsp) genes within one topologically associated domain in the genome of the Aedes aegypti mosquito. This Hsf1-sHsp cascade acts as an early response against chikungunya virus infection and shows pan-antiviral activity against chikungunya, Sindbis, and dengue virus as well as the insect-specific Agua Salud alphavirus in Ae. aegypti cells and against chikungunya virus and O’nyong-nyong virus in Aedes albopictus and Anopheles gambiae cells, respectively. Our comprehensive in vitro data suggest that Hsf1 could serve as a promising target for the development of novel intervention strategies to limit arbovirus transmission by mosquitoes.